2020
DOI: 10.1097/ijg.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Tenon Cyst Patch Graft for Ahmed Glaucoma Valve Tube Exposure: Case Series Report

Abstract: Purpose: To report our experience using a Tenon cyst autograft in the management of tube exposure post Ahmed glaucoma valve (AGV) implantation. Methods: This is a retrospective case series. Results: Four patients who underwent tube exposure repair using Tenon cyst autograft were identified in our tertiary care center. The duration between initial AGV implantation and tube exposure ranged between 3 and 36 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 70 Using a Tenon cyst patch graft is another option for the surgical repairing of the tube exposure. 79 In this approach Tenon tissue harvested around the plate is used for the tube coverage.…”
Section: Complicationsmentioning
confidence: 99%
“… 70 Using a Tenon cyst patch graft is another option for the surgical repairing of the tube exposure. 79 In this approach Tenon tissue harvested around the plate is used for the tube coverage.…”
Section: Complicationsmentioning
confidence: 99%
“…Some authors have suggested using a different type of patch graft from initial surgery in cases of graft melt where there may be an underlying immunological reaction leading to the melt 34 . The type of grafts used for tube exposure repair include full thickness donor sclera, 15 split‐ thickness scleral flap, 54,55 cornea, 56 conjunctival pedicle flaps, 57,58 amniotic membrane, 59 donor acellular dermis, 60 buccal mucosa, 61 fascia lata, autologous tragal perichondrium patch graft, 62 tenon cyst patch graft, 63 and synthetic materials such as Ologen® 64 . Grover et al studied the safety and efficacy of forniceal conjunctival pedicle flap repair for conjunctival‐deficient tube erosions and in their retrospective study, none of their patients (15 eyes from 14 consecutive patients) had recurrence of tube erosion (mean follow‐up period was 49 months) 58 .…”
Section: Management Of Gdi Exposurementioning
confidence: 99%
“…Tenon cyst formation around implant is not an uncommon finding following GDI surgery and Alvarez‐Ascencio et al described excising the tenon cyst or capsule around the GDI plate and using it as an autograft to cover the exposed area. None of their four patients had re‐exposure at the end of follow‐up (patients were followed postoperatively for a range of 4–24 months, with a mean of 11.75 months) 63 . In a case series of eight patients who underwent tube revision surgery due to exposed tubes from conjunctival defects, successful and lasting closure of all eight conjunctival defects with Ologen® was achieved without any side effects or complications (follow‐up of 12–42 months).…”
Section: Management Of Gdi Exposurementioning
confidence: 99%